Preventive Health and Islamic Family Values: The Role of Tetanus Toxoid Vaccine Immunization in Promoting Sakinah Families - Iffa Dilla; Moh. Muhibbin; Dzulfikar Rodafi (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
A harmonious family is a family that can maintain peace and is based on love (mawaddah) and affection (rahmah). One of the main purposes of marriage is to continue the lineage, maintain human dignity, and foster a quality generation. Tetanus toxoid (TT) vaccine immunization injections for prospective brides play an important role in maintaining the health of the mother and fetus from tetanus infection, which can cause disability and even death. Indirectly, tetanus toxoid vaccine immunization injections sociologically have an important correlation in forming a harmonious family. A harmonious family is not formed automatically, but is the result of various interrelated factors that are continuously maintained. The combination of religious values, psychosocial stability, health, economy, and social support greatly determines the success of forming a harmonious, loving, and compassionate family. This study uses a quantitative approach with a mixed methods method, namely a combination of numerical data analysis and qualitative exploration, in order to obtain a more comprehensive understanding of the phenomenon being studied. The main focus of this study is to examine the relationship between the implementation of TT vaccination injections and the formation of a harmonious family, accompanied by interviews and observations to explore the supporting factors that influence this correlation